Analisis Berpikir Kreatif Siswa Menggunakan Metode Pembelajaran Project Based Learning - Nailufari, Nadiefa Nissaul Afni; Septiani, Afi Khusnul; Dato, Anselmia Aprilin Kartini; Lesmono, Albertus Djoko (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to analyze the level of creative thinking of students in class X.5 at SMA Negeri 1 Jember. Through a descriptive research approach and using project-based worksheets as a data collection instrument to assess fluency, flexibility, originality, and elaboration in students' creative thinking. The results showed variations in the level of creative thinking among students, who were divided into six groups. Further analysis based on the creative thinking indicators revealed that on fluency, most students showed sufficient and creative levels of creativity. On flexibility, most students showed a good level of creativity, while on originality and elaboration, students showed a very high level of creativity. The relevance of this research is the importance of learning differentiation to adjust students' creativity level. Teachers can develop learning strategies that are more in line with each student's creative potential, including the use of teaching methods that introduce flexibility, original idea generation, and the development of elaboration skills. The project-based assessment system can also be improved to measure aspects of creative thinking more comprehensively. This research is expected to contribute to the understanding of student creativity at the senior high school level and open the door for further research in the context of creative thinking